2019
DOI: 10.3390/su11154102
|View full text |Cite
|
Sign up to set email alerts
|

Planning an Intermodal Terminal for the Sustainable Transport Networks

Abstract: Growing competition in the global market imposes the need for adequate planning of transportation processes and development of intermodal transport networks, whereby intermodal terminals play a key role. This paper proposes a methodology for prioritization of the intermodal terminal's development features, as the procedure in its planning process, leading to the design of the intermodal terminal in accordance with the needs of various stakeholders and the principles of the sustainable development. As the stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The remoter rural areas, where income levels are generally low and economic opportunities limited are in most need of initiatives to increase accessibility [51]. Similar analyses could be conducted in the peripheral regions of countries along the eastern and southern borders of the EU, where the decision makers are likely to "provide inaccurate, vague or ambiguous assessments due to the incomplete information or inability of their processing in the given circumstances" [52]. The applied methodology, including the measures of the presented indices, can be applied to draft regional and sub-regional transport policies, plan transport services, and introduce an integrated planning approach to the transport development.…”
Section: Discussion Summary and Conclusionmentioning
confidence: 99%
“…The remoter rural areas, where income levels are generally low and economic opportunities limited are in most need of initiatives to increase accessibility [51]. Similar analyses could be conducted in the peripheral regions of countries along the eastern and southern borders of the EU, where the decision makers are likely to "provide inaccurate, vague or ambiguous assessments due to the incomplete information or inability of their processing in the given circumstances" [52]. The applied methodology, including the measures of the presented indices, can be applied to draft regional and sub-regional transport policies, plan transport services, and introduce an integrated planning approach to the transport development.…”
Section: Discussion Summary and Conclusionmentioning
confidence: 99%
“…Some of the disadvantages are the need for multiple repetition of the questionnaire to achieve the convergence of the assessments and the high cost of data collection, especially for large and complex problems [56]. The Delphi method is widely accepted in the literature, and either alone or in combination with some other methods it has been used to solve various problems, such as defining the typical structures of the intermodal terminals [57], selecting the development indicators of the urban sustainability [58], planning of intermodal terminals [59], selecting the maintenance strategy for ship machinery systems [60], locating intermodal terminals [61], etc.…”
Section: An Overview Of the Methods That Make Up The Mcdm Modelmentioning
confidence: 99%
“…Finally, a data set of 71 publications were included in the review. A brief review of the literature that was published following the period of study indicated that articles were published that outlined decision frameworks and decision models for the planning and design of sustainable urban transport systems (e.g., [41][42][43][44][45]). However, recent articles could not be found to describe an indicator framework for microtransit systems, or that would significantly influence the results of this indicator framework.…”
Section: Methods Overviewmentioning
confidence: 99%